Pd‐Lined Strained Trimetallic Au‐Ag‐Pd Nanoprism for Enhanced Electrocatalytic Activity Towards Formic Acid Oxidation - Sourav Mondal; Sandip Kumar De; Tanmay Ghosh; Subrata Mondal; Mihir Manna; Dulal Senapati (Small Science)
Formic acid oxidation (FAO) reaction is an important electrocatalytic reaction in low‐temperature proton exchange membrane fuel cells. Pd‐based material has a superior electrochemical activity towards FAO. The activity of Pd‐based bimetallic materials is also well‐studied in the literature. Here, we have reported the synthesis of a unique heterostructured trimetallic nanoparticle where Pd is lined along with Ag forming a certain percentage of alloy at the edges of the bimetallic Au‐Ag prismatic nanotemplate. Though Pd acts as an effective material, this unique structure shows much improved catalytic activity due to the synergistic effect of Au, Ag, and Pd. Pd deposition increases the surface roughness and electrochemically active surface area. Lattice strain due to lattice mismatch between Ag and Pd modifies the d‐band center, enhancing the intrinsic activity, and facilitating the reaction kinetics. Pd‐deposited nanoparticle shows 3.4 and 4 times higher ECSA than monometallic cubic Pd nanoparticles and commercially available 10 wt% Pd/C. Our synthesized best catalyst Pd‐1.5 shows the mass activity of 634 Ag−1 which is ≈7 times higher than the standard 10 wt% Pd/C. Our catalyst shows higher stability and CO‐tolerance due to the suppression of the dehydration pathway and the reaction proceeds mainly via the dehydrogenation pathway.